Application of Organizational Behavior Concepts in the Socialization of Child Legal Protection and Responsible Use of Social Media: Study at Pondok Pesantren Tahfizh Qur'an Bina Masyarakat Mandiri - Satiadharmanto, Deddi Fasmadhy; Afiat, M; Shaleh, Sulaeman As; Zamzanie; Rahmalia (International Humanity Advance, Business & Sciences, 2024)
This community service activity by the students of the Faculty of Law, Universitas Tangerang Raya, discusses the application of Organizational Behavior concepts in the socialization of child legal protection and responsible use of social media at Pondok Pesantren Tahfizh Qur'an Bina Masyarakat Mandiri. The aim is to enhance the students’ understanding of children's rights and responsible use of social media, as well as to analyze the application of organizational behavior principles in the activities. The methods used include lectures, discussions, and Q&A sessions. The results indicate that this activity successfully applied various aspects of Organizational Behavior, such as organizational communication, learning and development, change management, ethics and social responsibility, teamwork, adaptation to the environment, and motivation. In conclusion, the principles of organizational behavior can be effectively applied in the interaction of organizations with the wider community, especially in efforts to increase legal awareness and responsible use of social media among students at the pesantren.